Pengembangan Media Audio Visual dan Alat Peraga dalam Meningkatkan Pemahaman Konsep dan Pemecahan Masalah - Fransina Thresiana Nomleni; Theodora Sarlotha Nirmala Manu (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2018)
The purpose of the research is to produce teaching material of props from scrap materials for system human feasible and practical to be used as a medium of learning in enhancing students' understanding of the concept. The type of research was research and development. ADDIE model used in this reseach contained: 1) Analysis 2) Design 3) Development 4) Implementation and 5) Evaluation. Questionnaire and tests were used as the instruments in data collection. The data analysis in questionnaire forms were statistically using percentage and t test. Pre-test and Post test designed into two groups. Based on the evaluation from the content experts, the value of the material was 82%, 92.85% for instructional media, while instructional design was 87.5%. For the small group the media, it reached up to 84.25%, the field pre-experimment group was 87.89%, while the use of user guide was 87.5%, 85% of instructional media experts, instructional design experts 79.17 %%, the small group bievaluation 84.25%, compared to the experiment group in big number was 86.44%. the result for evaluation of the props materials used were catagorized as excellent. It means t-test for the use of teaching material was equal to 3,586 with sig. of α = 0.005, t = 2.704. The value of t arithmetic less than t table (3.586> 2.704). It was said that the props of scrap materials improved students' understanding of the concept. The indicator for the concepts include memorizing, understanding, and applied to show that there was increasing in the value of the pre-test and post-test the student.